PENGEMBANGAN MEDIA BIMBINGAN STACKO HOLLAND UNTUK MENINGKATKAN WAWASAN KARIR PADA SISWA SMA - Izzah Nur Salima; Arga Satrio Prabowo; Alfiandy Warih Handoyo (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2022)
The research was conducted with the aim of developing a game media that can be used as a support when providing information about careers in career field group guidance services for high school students. This is expected to make it easier for teachers of BK to improve students' career insights at school. This research was conducted at SMAN 5 Kota Serang with the target of class XI students. The method used is research and development with a 4D development model. The results of the validity test of the questionnaire used to determine the number of career insights of students resulted in the loss of seven of the 55 statement items with a reliability score of 0.683. The results of the media expert test were 82.18%, the material expert validation was 100%, and the linguist validation was 92.5%. The product feasibility test was carried out involving 12 people with an average score of 33% for increasing career insight. Media Stacko Holland is an innovation in guidance and counseling that is very inspiring, especially in terms of an attractive appearance, easy to understand, and according to the needs of students.